Quadruple Series Equation InvolvingGeneralized- BatemanK- Functions - Rajendra Kumar Tripathi, Prof. C.K. Dixit (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Formal solution four series equation involving generalized Bateman k Functions is given is this paper. Finally, the solution of four series equation is reduceto Freadholm integrals equation of second time in one independent which can be solve by some numerical method.